Hypothyroidism with true myotonia. Issue 11 (November 1978) - Venables, G S; Bates, D; Shaw, D A
Abstract : A patient with subclinical hypothyroidism who presented with true myotonia is described. There was no evidence that either he or members of his family had dystrophia myotonica or myotonia congenita. Treatment with thyroxine resolved his symptoms completely.